2011
DOI: 10.1007/s10620-010-1529-2
|View full text |Cite
|
Sign up to set email alerts
|

Pre-transplant Kidney Function Predicts Chronic Kidney Disease After Liver Transplant: Meta-Analysis of Observational Studies

Abstract: An increased risk of chronic kidney disease frequently exists among liver transplant recipients with reduced renal function at transplant. The occurrence of chronic kidney disease after liver transplantation has a major impact on mortality. Additional studies are needed to understand better the natural history of chronic kidney disease among liver transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 42 publications
1
24
0
3
Order By: Relevance
“…2,3,7,11,23,24,28,35,36 However, it should be pointed out that our results could have been influenced by the small number of cases of CKD stages 4 and 5. On the other hand, renal dysfunction in the first six months post-LT was associated with CKD and mortality in the first two years after LT in this study.…”
Section: B Discussionmentioning
confidence: 65%
“…2,3,7,11,23,24,28,35,36 However, it should be pointed out that our results could have been influenced by the small number of cases of CKD stages 4 and 5. On the other hand, renal dysfunction in the first six months post-LT was associated with CKD and mortality in the first two years after LT in this study.…”
Section: B Discussionmentioning
confidence: 65%
“…Additionally, serum Cr in cirrhotic patients who have less muscle volume than healthy controls was not shown to accurately reflect renal function [30,31]. However, renal dysfunction can predict progressive mortality in cirrhotic patients [30,31], and poor pre-transplant renal function can predict chronic kidney disease after LT [32]. It has not been previously shown that a small elevation of Cr in cirrhotic patients in pre-LT is a prognosis factor after LT. Our study suggests that a low serum level of Cr can be a useful predictor of survival after LT and may reflect liver function more accurately than renal function before LT.…”
Section: Discussionmentioning
confidence: 99%
“…A stratified analysis including only studies provided with baseline GFR, revealed that the summary estimate of RR and 95% CIs for occurrence of chronic renal failure after liver transplantation in patients with diminished renal function at transplantation was 2.12 (95% CI, 1.01-4.46, p=0.01) (Fabrizi et al, 2011). Even relatively mild elevations in pre-transplant creatinine >1.5 mg/dL may portend poor long term renal function.…”
Section: Pretransplant Renal Dysfunctionmentioning
confidence: 98%
“…Overall risk of CKD development (eGFR < 60 mL/min/1.73 m 2 ) was associated with high Child-Pugh score and high Model for End-Stage Renal Disease (MELD) score (Lee et al, 2010). Especially in recipients whose pre-operative eGFR was high (>or=60 mL/min/1.73 m 2 ), rapid progression of kidney disease was associated with Child-Pugh score (in addition to high tacrolimus level and posttransplant acute renal failure) (Fabrizi et al, 2011).…”
Section: Child-pugh Score and High Model For End-stage Renal Disease mentioning
confidence: 99%